Pengaruh Tazkiyatun Nafs dalam Pengendalian Emosi Menurut Perspektif Islam - Rahaja Raditiya; Akhmad Affandi (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
In Tazkiyatun Nafs is a concept of purification of the soul that aims to cleanse oneself of diseases of the heart and despicable morals, so that a Muslim can reach a higher spiritual state and obtain inner peace. Emotional control, in the Islamic context, refers to the ability of a Muslim to manage and direct the emotions that arise in him in accordance with the principles of Islamic teachings.    The purpose of this literature review article is to explore and explain the influence of tazkiyatun nafs, which is self-purification in a spiritual and psychological context, on emotional control from an Islamic perspective. This article uses a literature review approach. The literature search was conducted online through Google Scholar which was limited from 2012-2022 with the search process using the keywords “tazkiyatun nafs”, “self-control”, “Islamic perspective”. The analysis conducted by researchers can be concluded that tazkiyatun nafs is a powerful concept in Islam that focuses on spiritual purification and self-control as a means of controlling emotions. However, this article also highlights some weaknesses in the application of Tazkiyatun Nafs, including the high commitment required and the challenges in understanding the concept. Some people may experience difficulties in managing their negative emotions despite their efforts to apply Tazkiyatun Nafs.The importance of understanding and using Tazkiyatun Nafs to control emotions from an Islamic perspective is a key point emphasized in this article. In an effort to achieve emotional balance and inner peace, Tazkiyatun Nafs can be a powerful tool to shape a wiser and more compassionate individual.